Upaya Peningkatan Kemampuan Siswa dalam Memahami Soal Cerita Perkalian dengan Metode RME Kelas III Sekolah Dasar Negeri 1 Ketileng - Khoiriyah, Zumrotul A’la; Aminah, Siti Nur; Permatasari, Dewi; Hanik, Elya Umi (Lembaga Yasin AlSys, 2021)
The purpose of this study was to improve the ability to understand multiplication story problems for third grade students of SDN 1 Ketileng using the RME (Realistic Mathematics Education) approach. This type of research is Classroom Action Research (CAR) with two cycles. Each cycle consists of planning, implementing actions, observing, and reflecting. The subjects of this study were teachers and third grade students of SDN 1 Ketileng, Todanan District, Blora Regency. Data collection techniques through observation, interviews, tests, and observations. Based on the results of the study, it showed that the students' multiplication ability had increased which could be seen from the results of each cycle. This can be seen from the percentage of students' complete scores who reach > 65 (KKM). In the pre-cycle the number of students who completed there were 45%. In the first cycle the number of students who completed there were 65% an increase of 18%. In Cycle I to Cycle II to 82% an increase of 19%. It can be seen from the results of Cycle II, the number of students who obtained a complete score > 65 at least 80% has been achieved.